Essentials of modern spectrum management - Cave, Martin (Cambridge University Press, 2007)
This is the first book to describe and evaluate modern spectrum management tools.
Keywords: Wireless communication systems.; Wireless communication systems -- Economic aspects.; Radio frequency allocation.; Signal processing.; elektronické knihy; electronic books